2022
DOI: 10.1039/d2qo01224c
|View full text |Cite
|
Sign up to set email alerts
|

Silver-mediated annulation between 5-H-1,2,3-thiadiazoles and 1,3-dicarbonyl compounds to construct polysubstituted furans

Abstract: An efficient synthesis of polysubstituted furans by Ag(I)-mediated annulation between 5-H-1,2,3-thiadiazoles and 1,3-dicarbonyl compounds was reported. The methodology was characterized by availablility of starting materials, good functional group tolerance, and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 99 publications
0
5
0
Order By: Relevance
“…Transition metal-catalyzed denitrogenative transformations of 1,2,3-thiadiazoles have been demonstrated to be a facile and highly efficient approach to access structurally diverse heterocycles, [1][2][3] including thiophenes, [4][5][6][7][8] thiazoles, 9 isothiazoles, [10][11][12] 4H-thiopyran-4-ones, 13 thiochromenones, 14 1,3-thiaphospholes 15 and furans. 7,16 The mechanism of denitrogenative 1,2,3-thiadiazole transannulation reactions was investigated by Bao in 2021 using density functional theory (DFT) calculations, 17 with the structure of the key cyclometalated Rh(III) intermediate recently confirmed by our group using crystallographic data. 7 The general mechanism involves initial 1,2,3-thiadiazole ring-opening and subsequent denitrogenation, leading to formation of the cyclometalated organorhodium intermediate (Scheme 1a).…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal-catalyzed denitrogenative transformations of 1,2,3-thiadiazoles have been demonstrated to be a facile and highly efficient approach to access structurally diverse heterocycles, [1][2][3] including thiophenes, [4][5][6][7][8] thiazoles, 9 isothiazoles, [10][11][12] 4H-thiopyran-4-ones, 13 thiochromenones, 14 1,3-thiaphospholes 15 and furans. 7,16 The mechanism of denitrogenative 1,2,3-thiadiazole transannulation reactions was investigated by Bao in 2021 using density functional theory (DFT) calculations, 17 with the structure of the key cyclometalated Rh(III) intermediate recently confirmed by our group using crystallographic data. 7 The general mechanism involves initial 1,2,3-thiadiazole ring-opening and subsequent denitrogenation, leading to formation of the cyclometalated organorhodium intermediate (Scheme 1a).…”
Section: Introductionmentioning
confidence: 99%
“…13 However, the harsh conditions, that is in the presence of nBuLi at −60 °C, significantly inhibit its synthetic applications. Owing to our continuous interest in the transformations of 1,2,3-thiadiazoles, 12,14 considering the rare report and the lack of exploration of synthetic applications of alkynylthio nucleophile intermediates, we wondered whether the in situ formed alkynylthiolate anion intermediate could be used for transition-metal catalyzed cross-coupling reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Among the different types of building blocks examined for denitrogenative annulation, diazocarbonyl compounds and 1,2,3‐triazoles are relatively well explored, allowing a range of oxygen‐ and nitrogen‐containing heterocycles to be accessed [7] . In 2016, the seminal work of Gevorgyan demonstrated that rhodium‐catalyzed denitrogenation of 1,2,3‐thiadiazoles is possible, allowing arrange of valuable sulfur‐containing heterocycles to be synthesised, [8] including thiophenes, [8a,9] thiazoles, [10] isothiazoles, [11] 4 H ‐thiopyran‐4‐ones, [12] thiochromenones, [13] 1,3‐thiaphospholes [14] and furans [9c,15] . The increasing application of 1,2,3‐thiadiazoles in synthesis has led to a range of synthetic approaches to 1,2,3‐thiadiazoles being developed [8d,11c,16] …”
Section: Introductionmentioning
confidence: 99%